Impact of language learning software on hearing-impaired students’ language skills - Rubashini Ramakrishnan,; Norshidah Mohamad Salleh,; Aliza Alias, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This paper discusses the impact of language learning software that was developed for hearing-impaired students for the Malay Language. The software was developed using Microsoft PowerPoint on a topic of reinforcement words with sign language. This study conveyed an experimental research design using pre-test and post-test of 8 hearing-impaired year 6 students that were selected randomly for this study. The study was conducted at one of the primary schools in Hulu Langat in Selangor. The pre and post-test analysis were based on the mean score value. The mean score value increased from 10.3% to 86.4% for multiple-choice questions and increased from 4.2% to 91.7% for sentence structure questions for the post-test analysis. The finding of this study found that students were able to choose appropriate reinforcement words for multiple-choice questions. The study also showed that students were able to construct sentences using appropriate reinforcement words. The implications of the study showed that learning software with interactive elements using sign language and attractive visuals can help hearing-impaired students to improve their understanding on reinforcement words. The usage of technology in various aspects of multimedia along with sign language video also helps to enhance the language skills of hearing-impaired students especially for those who practise visual learning styles. In conclusion, studies that focus on teaching using learning software with exciting elements are encouraged in the future.